On Effective Implementation of Recognition Algorithms for Calculating Estimates - D. S. Sargsyan (ՀՀ ԳԱԱ հրատ.)
In this paper the exact values of the ranks for some systems of supporting sets are calculated. A general method for constructing effective algorithms is suggested. Հաշվվում են ռանգերի ճշգրիտ արժեքները որոշ օգնող բազմությունների համար։ Առաջարկվում է արդյունավետ ալգորիթմների կառուցման ընդհանուր մեթոդ։Вычислены конкретные значения рангов для некоторых систем опорных множеств. Предлагается общий подход построения эффективных алгоритмов.
Keywords: Mathematics; Science